2021
DOI: 10.1088/1742-6596/1764/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of Chemistry Learning Outcomes of MAN 1 Cirebon City Student On the Material Structure of the Atom-Based Qurani Students Worksheet (LKPD)

Abstract: This study aims are to determine the increase and percentage in learning outcomes of the Chemical on the material structure of the atom through the use of Qurani Students Worksheet (LKPD) in the students of grade tenth Science 3 of MAN 1 Cirebon City on the academic year 2018/2019. The research method is classroom action research cyclical. The subject of the research is the students of grade tenth science 3 of MAN 1 Cirebon City on the academic year 2018/2019. The technique of collecting data is the test and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…The research results by Purnamasari et al (2018) showed that student worksheets could increase understanding of the material, increase collaboration, and activate the student learning process during group discussion activities. Research Azizah et al (2021) also proves that using student worksheets can help students add information about the concepts of the material being studied and can improve CLO. The potential of student worksheets-assisted PBL for cooperation and students' CLO has yet to be discovered in biology learning.…”
Section: Introductionmentioning
confidence: 90%
“…The research results by Purnamasari et al (2018) showed that student worksheets could increase understanding of the material, increase collaboration, and activate the student learning process during group discussion activities. Research Azizah et al (2021) also proves that using student worksheets can help students add information about the concepts of the material being studied and can improve CLO. The potential of student worksheets-assisted PBL for cooperation and students' CLO has yet to be discovered in biology learning.…”
Section: Introductionmentioning
confidence: 90%